2014
DOI: 10.3389/fneur.2014.00076
|View full text |Cite
|
Sign up to set email alerts
|

The Sub-Classification of Amnestic Mild Cognitive Impairment Using MRI-Based Cortical Thickness Measures

Abstract: Background: Amnestic mild cognitive impairment (aMCI) is considered to be the transitional stage between healthy aging and Alzheimer’s disease (AD). Moreover, aMCI individuals with additional impairment in one or more non-memory cognitive domains are at higher risk of conversion to AD. Hence accurate identification of the sub-types of aMCI would enable earlier detection of individuals progressing to AD.Methods: We examine the group differences in cortical thickness between single-domain and multiple-domain sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
4
9
1
Order By: Relevance
“…In addition to bilateral MTL atrophy, multidomain amnestic MCI typically involves widespread thinning within parietal, temporal, and frontal regions. 17,18,20,21 However, the pattern of thinning in the dysexecutive/ mixed MCI group was less consistent with previous studies of the conventional nonamnestic MCI subtype, in which heterogeneous patterns of gray matter loss and less MTL focus have been noted. 17,18 The current study did not include a purely dysexecutive group, as all subtypes demonstrated memory impairment, limiting our ability to examine nonamnestic forms of MCI.…”
contrasting
confidence: 32%
“…In addition to bilateral MTL atrophy, multidomain amnestic MCI typically involves widespread thinning within parietal, temporal, and frontal regions. 17,18,20,21 However, the pattern of thinning in the dysexecutive/ mixed MCI group was less consistent with previous studies of the conventional nonamnestic MCI subtype, in which heterogeneous patterns of gray matter loss and less MTL focus have been noted. 17,18 The current study did not include a purely dysexecutive group, as all subtypes demonstrated memory impairment, limiting our ability to examine nonamnestic forms of MCI.…”
contrasting
confidence: 32%
“…Various types of cortical morphological features, such as cortical thickness, GM volume, metric distortion, and GM densities, have shown promising capacities for the classification between aMCI and controls [43][44][45]. Our study revealed the relatively high classification accuracy by using each of parameters extracted from the whole brain (GM volume and density), which was in line with previous studies.…”
Section: The Reliability Of Combined Visual Rating Scalessupporting
confidence: 90%
“…Mild cognitive impairment (MCI) is understood as a risk state for dementia [1][2][3][4][5]. MCI patients could progress to dementia (from 4 to 15% in clinical setting [6] and from 4 to as high as 17% in community-based studies [7]), could remain stable or could even revert to a normal cognition [4,[8][9][10][11][12]. It is a current target to identify those who hold a high risk of progressing to dementia to provide interventions that can prevent or slow further cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this notion is the subtype of MCI that presents with memory and other cognitive impairments (multidomain amnesic MCI, maMCI), with executive functions being those more commonly affected [9,25]. Some studies pointed out that maMCI exhibits the fastest progression to dementia in ACS in longitudinal studies [4,11,12]. Notwithstanding, the evidence remains mixed with some studies showing that dysexecutive MCI holds a higher risk to progress to dementia in ACS [2], while others concluded that amnestic and maMCI had a similar risk of conversion to that dementia [26].…”
Section: Introductionmentioning
confidence: 99%